Analysis of HPV DNA Screening Results Distribution for Early Detection of Cervical Cancer at Poasia Community Health Center - Fadilatulsyam; Hasnianti; Isnaeni Salamiyah (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Cervical cancer is one of the leading causes of death in women worldwide, with the majority of cases caused by high-risk Human Papillomavirus (HPV) infection. Early testing through HPV DNA testing has proven to be a more sensitive method of screening than conventional cytology. Objective: This study aims to analyze the distribution of HPV DNA screening results as an early detection of cervical cancer at the Poasia Community Health Center in 2024. Methods: This type of study is descriptive, using secondary data from the medical records of HPV DNA tests taken during the period January to December 2024, with a total of 197 samples. Data analysis was carried out descriptively to evaluate the distribution of frequency and percentage of positive results based on age categories and HPV genotypes. Results: The study showed that there were 14 samples (7.1%) that were positive for HPV, with the most genotype being HPV 18 (5.1%), followed by HPV 16 (1.5%), other types (31, 33,35,39,45,51,56,58,59,66 and 68) (1.0%) and HPV 52 (0.5%). Of the total 14 HPV-positive samples, 12 (85.7%) showed single-type infection , and 2 (14.3%) double infection . The highest number of positive cases was found in the age group of 31 to 49 years (7.0%). Conclusion: HPV DNA-based screening has proven to be effective as an early detection method of cervical cancer in primary health services, so it is important to increase the capacity and referral system at Poasia Community Health Center to support the elimination of cervical cancer in Indonesia. Keywords: HPV DNA, cervical cancer, screening, genotype,adult, Indonesia